Peran Sustainability Reporting dalam Hubungan Profitabilitas dengan Nilai Perusahaan Sektor Consumer Non-Cyclical - Virginia Yuli Pratama; Januar Eko Prasetio (Owner : Riset dan Jurnal Akuntansi, 2026)
The consumer non-cyclical sector faces a dual challenge in the post-pandemic era in maintaining profit levels in a competitive market while simultaneously meeting the demands of investors who are increasingly critical regarding sustainability issues. This research aims to examine and analyze the role of sustainability reporting as a strategy to strengthen the influence of profitability on firm value. Using a purposive sampling method, 68 observations were obtained from companies listed on the Indonesia Stock Exchange for the 2022-2024 period. Data were analyzed using Hierarchical Moderated Regression Analysis. Profitability is measured through the ratio of net income to total assets, firm value is measured by the price to book value ratio, and sustainability reporting is assessed using a global reporting standard disclosure indeks 2021. The results show that profitability consistently has a positive and significant effect on firm value. However, Sustainability Reporting partially does not have a significant effect. Interestingly, the interaction test proves that Sustainability Reporting acts as a Moderator that significantly strengthens the relationship between profitability and firm value. This implies that in a competitive market, sustainability disclosure serves as a strategic "ethical validation" that captures market trust, thereby increasing the valuation of profitable companies. The results of this study provide input for management to integrate sustainability strategies into financial operations to achieve optimal market valuation.